Modern trends in serving and setting skills in elite volleyball - Kareva, Yu. Yu.; Nikolaeva, I. V.; Shikhovtsov, Yu. V.; Kudinova, Yu. V.; Ivanova, L. A. (Theory and Practice of Physical Culture, 2019)
The article gives analysis of the elite volleyball players` competitive performance data mined by educational surveys with video captures processed by computerized Data Volley-2007 system. Subject to analysis were 52 matches of Nova Volleyball Club (Samara Oblast) played in the Russian Super League Championships in 2016-2018. The study data cover the key qualitative and quantitative characteristics of the modern serving and setting skills. It was found that the top volleyball masters give preference to the jump power serves followed by floaters; power serve receiving and setting is commonly less successful than the floater setting; and most of the serves come from the right third of the serve zone. The study data give the means to analyze the key progress trends in the modern volleyball and show that that receiving and setting is efficient and accurate enough when the setter watches closely the serving opponent to guess the serve style and target by the first signs. Elite training systems must make due emphasis on the technical/ tactical skills exceling to facilitate the serve anticipation skills in setters for efficient defense.